KAJIAN RENCANA EVAKUASI DALAM KESIAPSIAGAAN BENCANA TSUNAMI DENGAN PENDEKATAN BERBASIS MASYARAKAT (STUDI KASUS: KECAMATAN MEURAKSA KOTA BANDA ACEH) - , Variadi ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The earthquake and tsunami in December 2004 has caused different level of destruction in Indonesia and numbers countries in Asian region. The widerange of tsunami affects have stimulated the implementation of disaster mitigation program namely Tsunami Early Warning System Program, Evacuation Facilities Development Program, Evacuation Plan Program, Disaster Hazard Mapping and numbers of disaster management related program in the tsunami affected region. The mitigation programs were mostly developed based on scientific studies and using more technical approaches. The crucial question is whether community awareness on disaster potential and understand those programs that were implemented around them. Furthermore, how far those programs involved community members and in which level, so that it can be useful for the community members. This thesis will focus its studies in the communities socio-culture aspect in understand and utilize of the disaster mitigation related facilities and the evacuation plan. This research was using field observations, semi-structured interviews and community consultation in 1 (one) of the tsunami most affected areas Meuraksa sub district, Banda Aceh, Province of Aceh, Indonesia. The research was started by: (1) collecting data related to the evacuation plan available, (2) listing escape buildings and evacuation route, (3) evacuation plan analysis towards the facilities and (4) in the community level, the research collected information about communityâs perception, knowledge and understanding towards evacuation plan including the planning, dissemination and implementation processes. The observation results show that period to develop evacuation plan was for short term until 2010, the existing evacuation facilities is in poor condition and furthermore there are different reality between the overall disaster mitigation plan for Meuraksa sub district with communities perceptions and needs. The semistructured interviews and community consultation processes show that community understand the evacuation plan by instinctive, but reported that they never comprehensively involved in the evacuation planning, dissemination and implementation processes that make the community not well organized. This was shown in the average of community disaster preparedness index which is 3,09 (scale 4,00) base on evacuation plan. From various data analysis occurred that several factors need to be modified. They are internal factor which starts from planning to the simulation of evacuation plan like tsunami drill and the external factor which is understanding and perception from the community themselves. Evacuation plan modifications need to be processed through different stages. It starts from evacuation plan review, problems and resources, solution and idea inventory as well as the dissemination process which using community based approaches. Individual evacuation protocol could be alternative solution to be implemented well organized to increase number of survivor and the limitation of vertical evacuation facilities.